2020
DOI: 10.3389/fpsyt.2020.00273
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems Influence Emotional/Behavioral Symptoms and Repetitive Behavior in Preschool-Aged Children With Autism Spectrum Disorder in the Unique Social Context of China

Abstract: Sleep disturbances are common in people with autism spectrum disorder (ASD), but research on this topic is still limited in China. In the current study, we evaluated the prevalence of sleep problems in preschool-aged children with ASD and to examine the correlations between sleep disturbances and emotional/behavioral symptoms and repetitive behavior in the unique social context of China. This study recruited 475 preschool-aged children aged 3-6 years old, including 252 children with ASD (mean age 5.13 ± 1.15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
(108 reference statements)
0
21
1
Order By: Relevance
“…Some studies have reported that girls with ASD may exhibit reduced sleep duration 41 , 42 ; however, this is not consistent with our present findings. Other demographic factors (for example, parental education levels) seemed to be unrelated to the presence of sleep problems in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have reported that girls with ASD may exhibit reduced sleep duration 41 , 42 ; however, this is not consistent with our present findings. Other demographic factors (for example, parental education levels) seemed to be unrelated to the presence of sleep problems in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“… Poor sleepers had significantly higher irritability (t(2.85), p = 0.005), hyperactivity/noncompliance (t(3.11), p = 0.002) than good sleepers. 10 Kang et al (2020) 46 China Examined the relationship bet. sleep disturbances and emotional/ behavioral problems, and repetitive behavior ASD (n=252), M (80.6%), aged 3–6 M = 5.13 SD = 0.097 DSM V & CARS.…”
Section: Resultsmentioning
confidence: 99%
“…In Model 1, multiple regression analysis demonstrated that children with suspected sleep disorders assessed by the BCSQ tended to have more emotional and behavioral problems as assessed by the SDQ, indicating a negative association of sleep disorders with emotional and behavioral problems in children. Actually, the pathophysiological linkage between neurodevelopmental disorders and sleep disorders has not been fully elucidated, although children with ADHD and ASD are reported to have higher comorbidity for sleep disorders such as insomnia, circadian sleep–wake disorders, sleep-related respiratory disorders, restless leg syndrome, and periodic limb movement disorders 46 48 .…”
Section: Discussionmentioning
confidence: 99%